Java goes business class. (Visix Software's Vibe DE 1.0 Java business application development tool)(Application Development special section) - Jurvis, Jeff (InformationWeek (Manhasset, N.Y.), 1997)
Visix Software's $49.95 Vibe DE 1.0 is a state-of-the-art Java application development tool that features object-oriented class libraries but lacks comprehensive data access and platform support. Vibe operates on Windows NT, Windows 95 and Sun Solaris. Java code's platform-independent nature, however, requires applet user interfaces to conform to minimal common standards. Vibe's integrated development environment (IDE) is inferior to Symantec's and Microsoft's IDE standards in Visual Cafe and Visual J++, respectively, but Vibe offers superior class libraries to comparable Java IDEs. Visix provides Vibe's IDE with an interface editor and constructor, a project window and a debugger along with its Java compiler, run-time libraries, virtual machine and Sun's standard Java classes from Java Developer's Kit 1.0.2.